Analysis of Religious Studies: Getting to Know the Interpretation of the Al-Qur'an - Rambe*, Ali Sanusi; Harahap, Khoirul Saleh; Silalahi, Mawan Rinaldi (Universitas Syiah Kuala, 2023)
The history of the Qur'an is needed by humans, there are life instructions that are needed by humans as a guide in living life. The instructions in the Qur'an do seem to be still general and global, therefore it needs interpretation, related to the many problems of interpretation so that it requires reference to the History of the Qur'an, understanding the methodology of interpretation, namely the tahlili method, the ijmali method, the muqarin method, and the maudlu'i method. and know the forms of interpretation of the Qur'an such as Tafsir bi al-Ma'tsur, Tafsir bi ar-Ra'yi, Tafsir Isyari, as instructions and laws that exist in the Qur'an, because the Qur'an is passed down and intended for reasonable people. Tafsir is a variety of activities that seek to reveal human responses, reasoning, and ijtihad in order to reveal the most precise and clear meanings contained in the Qur'an so that humans can understand what the Qur'an explains both implicitly and expressly.